Characterization and properties of Palm Kernel Shell filled low density Polyethylene Biocomposites - Romisuhani Ahmad (School of Materials Engineering, 2011)
The prime objective of this study is to determine the properties and characterizations of palm kernel shells (PKS) filled low density polyethylene (LDPE) on a different composition.